Latent profile of personality traits for American older adults and its transition during the COVID-19 pandemic - Fu, Mingqi; Guo, Jing; Kang, Hao; Huang, Xiaorui (Frontiers in Psychiatry, 2024)
Background The impact of COVID-19 on older adults’ personality development is essential for emergency management but under-researched. This study seeks to explore the personality profiles of older adults living in the United States and how these profiles transitioned during the pandemic. Methods Longitudinal data were collected from 3,550 adults aged 60 and older who participated in both the 2016 and 2020 waves of the Health and Retirement Survey (61.18% female, mean age 65.85 in 2016). Personality traits were assessed using the Midlife Development Inventory. COVID-19-related experiences including pandemic concerns, restricted healthcare access, financial instability, work challenges, disrupted social connections, and mutual aid behaviors. Latent Profile Analysis and Transition Analysis were used for analysis. Results Three distinct personality profiles were identified: Well-adjusted, Moderate-adjusted, and Poor-adjusted. About 42% of respondents experienced personality changes during the pandemic. Higher levels of COVID-19 concern were linked to an increased likelihood of transitioning to Poor-adjusted from Moderate (OR=1.06, p<0.05) or Well-adjusted (OR=1.05, p<0.01). Challenges such as healthcare delays and financial hardships hindered transitions from Poor- to Moderate-adjusted (Healthcare delay: OR=0.39, p<0.05; Financial hardships: OR=0.67, p<0.05) but increased the likelihood of Moderate-adjusted individuals transitioning to Poor-adjusted (Healthcare delay: OR=1.46, p<0.05; Financial hardships: OR=1.51, p<0.05). However, Poor-adjusted individuals who provided help to others were more likely to transition to Moderate-adjusted (OR=2.71, p<0.01). Conclusions Personality transitions during crisis are significant among older adults. Future interventions should focus on addressing traumatic concerns, encouraging helping behaviors, and mitigating healthcare and financial challenges to support older adults’ personality development during crisis.